The balanced scorecard as a tool for environmental management: approaching the business context to the public sector - Monteiro, Sónia Silva; Ribeiro, Verónica Paula Lima (Anais do Congresso Brasileiro de Custos - ABC)
The balanced scorecard (BSC) model emerged in the business world as a tool to control social and environmental management, since it establishes a symbiosis between financial/economic and environmental/social goals. The aim of this paper is to present the different possibilities for the integration of environmental issues into the BSC, both in private and public entities. As in the private sector, the literature is not unanimous regarding the integration of environmental indicators into an independent perspective. The implementation of BSC model in the public sector requires double attention: on the one hand, because it is necessary to adapt it to the specificities of public entities, and on the other hand, because its environmental aim is different from and wider than that of the private sector.